Wild Lathyrus—A Treasure of Novel Diversity - Singh, Akanksha; Balech, Rind; Barpete, Surendra; Gupta, Priyanka; Bouhlal, Outmane; Tawkaz, Sawsan; Kaul, Smita; Tripathi, Kuldeep; Amri, Ahmed; Maalouf, Fouad; Gupta, Sanjeev; Agrawal, Shiv Kumar (MDPI, 2024)
Grasspea (Lathyrus sativus L.) is a climate-smart legume crop with adaptation to fragile agroecosystems. The genus Lathyrus is recognized for its vast genetic diversity, encompassing over 160 species, many of which are cultivated for various purposes across different regions of the world. Among these, Lathyrus sativus is widely cultivated as food, feed, and fodder in South Asia, Sub-Saharan Africa, and the Central and West Asia and North Africa (CWANA) regions. Its global cultivation has declined substantially due to the stigma posed by the presence of neurotoxin β-N-oxalyl-L-α, β-diaminopropionic acid (β-ODAP) in its seeds and green foliage. Overconsumption for a longer period of grasspea seeds harvested from landraces may lead to a neurological disorder called neurolathyrism in humans. ODAP is an obstacle for grasspea expansion, but crop wild relatives (CWRs) have been found to offer a solution. The incorporation of CWRs, particularly Lathyrus cicera, and landraces into breeding programs may reduce the ODAP content in grasspea varieties to a safer level. Recent advances in genomics-assisted breeding have expanded the potential for utilizing challenging CWRs to develop grasspea varieties that combine ultra-low ODAP levels with improved yield, stability, and adaptability. Further progress in omics technologies—such as transcriptomics, proteomics, and metabolomics—along with genome sequencing and editing, has greatly accelerated the development of grasspea varieties with reduced or zero ODAP content, while also enhancing the plant’s agronomic value. This review highlights the significance of utilizing CWRs in pre-breeding programs, and harnessing advanced tools and technologies to enhance the performance, adaptability, and resilience of grasspea in response to changing environmental conditions.